1978
DOI: 10.1161/01.cir.57.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous near closure of coronary artery fistula.

Abstract: An asymptomatic 14-year-old male was found at cardiac catheterization to have a coronary artery fistula involving a vessel originating from the left main coronary artery and terminating in the right heart. Chest X-ray and electrocardiogram were within normal limits and shunt flow was too small to be detected by oximetry although a large vessel was seen angiographically. One year later, the previously loud continuous murmur had disappeared and repeat catheterization demonstrated near closure of the fistula. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[8][9][10] In this case, progressive dilatation of the aneurysm to a diameter exceeding 5 cm suggested that the possibility of acute rupture was an indication for surgical resection, despite the small shunt ratio …”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In this case, progressive dilatation of the aneurysm to a diameter exceeding 5 cm suggested that the possibility of acute rupture was an indication for surgical resection, despite the small shunt ratio …”
Section: Discussionmentioning
confidence: 99%
“…The Konno criteria are commonly used as indications for surgery [19]:

left-to-right shunt ratio >30%, regardless of symptoms;

signs of ischemia or volume overload in the right ventricle on electrocardiography;

progression of pulmonary hypertension or congestive heart failure;

history of infective endocarditis;

aneurysm formation in the coronary artery.

Some authors [20] propose that asymptomatic CAVF could be surgically treated to prevent the occurrence of coronary artery disease or infective endocarditis. Although spontaneous CAVF closure has been reported in pediatric cases [21], spontaneous closure is unlikely in adults. CAAs >3 cm in diameter are at the risk of rupture [22].…”
Section: Discussionmentioning
confidence: 99%
“…In general, congestive car diac failure occurs only when communication is large and usually appears in the fourth decade or later. Other rare complications reported were myocar dial ischaemia, infective endocarditis, or rupture of the aneurysm [7], Although it seems clear that symptomatic patients with large communica tions should have their fistulae closed, the role of surgery in asymptomatic patients remains uncertain [19]. Closure can be done by simply ligating the fistula at its point of entry into the receiving chamber as was done in our case I. Alternatively, extracorporeal circulation may be used to achieve clo sure of the coronary artery fistula either from inside the involved chamber or via an arteriotomy, directly over the site of fistula [11], Many cases of successful operations involving coronary fistulae draining both into the right as well as the left side of the heart have been reported in the literature [7,11,20], Due to the presence of multiple fistulae involving all three major coronary arteries in our case 3, and the left anterior, descending and circum flex artery in our case 4, it was elected not to advise operation because of the great difficulties in ligating all the abnormal communicating channels to the left ventricle.…”
Section: Discussionmentioning
confidence: 99%